1988
DOI: 10.1002/ps.2780230305
|View full text |Cite
|
Sign up to set email alerts
|

The pyrethrins and related compounds. Part XXXIII. Effective combinations in the gemdimethyl‐central group region of non‐ester pyrethroids

Abstract: Synthesis and testing for insecticidal activity ofa wide range of combinations representing simultaneous variation in the acid or alcohol and central ffagments of non-ester pyrethroids reveals strong interactions between these changes, When the gemdimethyl (--CMe,--), or the equivalent cyclopropyl, group is present in the central chain rather than in a side chain, a new set of requirements for effective central groups applies; those identified as conferring highest activity in this situation are -CH=CH .CH,--;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…75) Meanwhile, Nissan Chemical found β-gem-dimethyl-β-phenylpropionic acid to be applicable as a pyrethroid acid, 76) even though similar structures such as α-gem-dimethylphenylacetates and α-gem-dimethylβ-phenylpropionates were nearly inactive. 77) Mitsui Toatsu found that gem-dimethyl derivatives lacking the carbonyl group of the ester linkage (namely, converting the ester linkage to the ether linkage) exhibited excellent insecticidal activity. 78) This finding led to the development of etofenprox, which had not only broad-spectrum insecticidal activity but also low fish toxicity.…”
Section: Beyond Cyclopropane and Ester Frameworkmentioning
confidence: 99%
“…75) Meanwhile, Nissan Chemical found β-gem-dimethyl-β-phenylpropionic acid to be applicable as a pyrethroid acid, 76) even though similar structures such as α-gem-dimethylphenylacetates and α-gem-dimethylβ-phenylpropionates were nearly inactive. 77) Mitsui Toatsu found that gem-dimethyl derivatives lacking the carbonyl group of the ester linkage (namely, converting the ester linkage to the ether linkage) exhibited excellent insecticidal activity. 78) This finding led to the development of etofenprox, which had not only broad-spectrum insecticidal activity but also low fish toxicity.…”
Section: Beyond Cyclopropane and Ester Frameworkmentioning
confidence: 99%